Characterising precipitate evolution in multi-component cast aluminium alloys using small-angle X-ray scattering - Panagos, P.; Wang, Y.; McCartney, D.G.; Li, M.; Ghaffari, B.; Zindel, J.W.; Miao, J.; Makineni, S.; Allison, J.E.; Shebanova, O.; Robson, J.D.; Lee, Peter D. (Elsevier, 2017)
Aluminium alloys can be strengthened significantly by nano-scale precipitates that restrict dislocation movement. In this study, the evolution of inhomogenously distributed trialuminide precipitates in two multi component alloys was characterised by synchrotron small angle Xray scattering (SAXS). The appropriate selection of reference sample and data treatment required to successfully characterise a low volume fraction of precipitates in multi-component alloys via SAXS was investigated. The resulting SAXS study allowed the analysis of statistically significant numbers of precipitates (billions) as compared to electron microscopy (hundreds). Two cast aluminium alloys with different volume fractions of Al3ZrxV1-x precipitates were studied. Data analysis was conducted using direct evaluation methods on SAXS spectra and the results compared with those from transmission electron microscopy (TEM). Precipitates were found to attain a spherical structure with homogeneous chemical composition. Precipitate evolution was quantified, including size, size distribution, volume fraction and number density. The results provide evidence that these multi-component alloys have a short nucleation stage, with coarsening dominating precipitate size. The coarsening rate constant was calculated and compared to similar precipitate behaviour.